n-fold implicative pseudo valuations on hoops - Yang, Yongwei (IJRDO -JOURNAL OF MATHEMATICS, 2018)
Hoops play an important role in the study of fuzzy logic based on t-norms. In this paper, we introduce some notions of n-fold implicative pseudo valuations on hoops, and also analysis some properties of them. The shrinkage property for n-fold implicative pseudo valuations is provided, and the preimage and image of n-fold implicative pseudo valuation are discussed.